2022
DOI: 10.1039/d2cs00640e
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent glycocyclopeptides: conjugation methods and biological applications

Abstract: In this review, we describe the conjugation methods used to construct multivalent glycocyclopeptides and their utilization for applications in glycoscience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 157 publications
1
19
0
Order By: Relevance
“…For synthesis and other examples of multivalent glycocyclopeptides, the interested reader is directed to a recent review of this issue reported by Renaudet and co-workers. 85…”
Section: Dendritic Cell-specific Intercellular Adhesion Molecule-3 Gr...mentioning
confidence: 99%
See 1 more Smart Citation
“…For synthesis and other examples of multivalent glycocyclopeptides, the interested reader is directed to a recent review of this issue reported by Renaudet and co-workers. 85…”
Section: Dendritic Cell-specific Intercellular Adhesion Molecule-3 Gr...mentioning
confidence: 99%
“…For synthesis and other examples of multivalent glycocyclopeptides, the interested reader is directed to a recent review of this issue reported by Renaudet and co-workers. 85 As an alternative to cyclopeptides, calixarene or its congener, thiacalixarene, manno- 86 or fucoclusters based on pseudopeptides or tetrahydroxamic acid-hydroxamic acids have been further investigated for the inhibition of DC-SIGN-dependent viral infections. 80,87 Both libraries of compounds contained strong inhibitors (in the nanomolar range) for the cis-infection of DC-SIGN-Jurkat cells by viral particles pseudotyped with Ebola virus glycoprotein (EBOVGP).…”
Section: Glycodendrimers and Glycodendronsmentioning
confidence: 99%
“…Click chemistry refers to rapid, spontaneous and highly efficient reactions between two chemical groups allowing for the incorporation of chemical groups with highly selective reactivity into small molecules or protein modifications without perturbing their biological function and with no membrane damage or undesirable side reactions (Peplow, 2019;Parker and Pratt, 2020). Click chemistry has become an essential tool for constructing biomolecular systems (Goyard et al, 2022).…”
Section: Click Chemistrymentioning
confidence: 99%
“…Copper-catalyzed azide alkyne cycloaddition, one of click chemistry, is a reaction between an alkyne and an azide that forms a triazole linkage (Goyard et al, 2022). Functional ligands c(RGDyK), the cyclo (Arg-Gly-Asp-D-Tyr-Lys) peptide, are conjugated onto exosomal surfaces through bio-orthogonal copper-free azide alkyne cyclo-addition and show high affinity to integrin αvβ3 in a mouse model (Tian et al, 2018).…”
Section: Click Chemistrymentioning
confidence: 99%
“…96 The synthetic strategy was cleverly executed using a modular approach with the synthesis of a trunk peptide synthesized with two masked aldehydes as 2-amino alcohol and acetal (42), a strategy advantageously used by Renaudet's group. 99 Successive unmasking of the aldehyde functionalities by treatment with sodium periodate (43) and trifluoroacetolysis (TFA) was followed by an oxime ligation with a hydroxylamine-containing Tn- (40) and TF-glycopeptide (41) gave Tn- (44) and TF-( 45) vaccines, respectively.…”
Section: Mucin-derived Glycoprotein and Glycopeptide Vaccine Conjugatesmentioning
confidence: 99%